Factors affecting customer loyalty of mobile RFID services in Korea - Park, Yong-Jae; Rim, Myung-Hwan; Lee, Seung-Koog (Technological and Economic Development of Economy, 2013)
Mobile radio frequency identification (RFID) services are expected to be launched in full-scale as a new service option in the telecommunications service market following the development of RFID technology and maturation of the IT infrastructure. Importance of customer loyalty has been widely recognized in business marketing for a long time, and the customer loyalty enhancement strategies for mobile RFID services is of significance to telecommunication carriers in terms of new business value creation. This study identifies the factors affecting customer loyalty for mobile RFID services and presents telecommunication service managers with information useful for improving customer loyalty for related new services. The data was collected from customers with some experience in the use of mobile RFID services through an online survey for an empirical analysis. And the collected data was analysed with structural equation model to verify the cause and effect relationship among perceived quality, switching cost, perceived value, customer satisfaction, switching barrier and customer relationship. The analysis showed that the quality of tag recognition and content quality proved to have a direct impact on the customer satisfaction, whereas connection quality and ease of use would rather indirectly than directly influence customer satisfaction by perceived value. Perceived value and satisfaction affected the loyalty. Adaptation cost affects switching barriers, the higher the switching barriers, the stronger the loyalty. Based on the results of the empirical analysis, practical implications were given. What is more, mobile RFID customers were divided into two groups that are favourably and unfavourably disposed toward the service, and suggested customer loyalty improvement strategies adapted for each group.